HUBUNGAN ANTARA KANDUNGAN LOGAM BERAT Pb, Cr DAN Hg DI SEDIMEN DAN KANDUNGAN LOGAM BERAT Pb, Cr DAN Hg DI DAGING DAN ORGAN IKAN DEMERSAL DAN PELAGIS DI PERAIRAN SUNGAI CILIWUNG - Khoe Susanto Kusumahadi; Yeremiah Rubin Tjamin (Gunung Djati Conference Series, 2023)
The heavy metals of Lead (Pb), Chrom (Cr), and Merkuri (Hg) are widely substances used in the industrial sectors including textile, manufacturing, printing, pharmacy, pesticide, painting, heavy equipment and leather. This industrial activities generally caused to the heavy metals pollution have been found located around of Ciliwung River. Basically, the waste water coming from that industrial activities discharge in stream without treatment causing the seriously River Pollution. That industrial waste water production continuously causing accumulation of heavy metals in the sediment and aquatic organism such as plankton, benthos. The goal of this study was to know the relationship between the heavy metal content of Pb, Cr, and Hg at the sediment and the content of Pb, Cr, and Hg in the organs and meat of Demersal fish and Pelagic fish that live in Ciliwung River waters. The results showed that Pb, Cr, and Hg were found in the sediments Ciliwung River. Concentrations Pb, Cr, and Hg at sediments were different significant (P<0.05) according to the location of observation, while according to the replication (observation time) only Hg was significantly different (P<0.05). Observations of heavy metals in fish showed that only Hg in the organs of Demersal fish were significantly different according to the location of observation and replication (time of observation). In general, the content of Pb, Cr, and Hg in the organs of Demersal fish and Pelagic fish is higher than that in meat. The relationship between heavy metal content in sediment and heavy metal content in fish showed that only the relationship between Cr content in sediment and Cr content in Demersal fish meat and the relationship between Hg content in sediment and Hg content in Pelagic fish meat was significantly different (P<0.05).